Dropshipping pada CV. Karya Utama Surabaya terhadap Pemberdayaan Kaffahisme Ekonomi Perspektif Hukum Islam - Syarifuddin Hidayatullah Hamdani (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2020)
This study examines the dropshipping activities carried out by CV. Karya Utama Surabaya in empowering economic kaffahism. This study uses a descriptive method with a qualitative approach. The collected data were analyzed using descriptive qualitative analysis method. The purpose of this study was to determine the implementation of dropshipping activities in empowering economic kaffahism and dropshipping practices with an Islamic perspective. The result of this research is the implementation of dropshipping has contributed to economic empowerment evenly. Dropship is allowed in Islam as long as there is no argument for prohibiting it by using the contract and its respective consequences such as the salam contract, wakalah and samsarah. The author suggests internet-based business and marketing players, in this case CV. Karya Utama Surabaya (supplier) and modern sales force (dropshipper). Among them, dropshippers are required to be able to provide the totality of services to anyone who is involved in the world of online buying and selling and marketing based on modern technology. Meanwhile, CV. Karya Utama Surabaya as a supplier must also be selective in choosing dropshippers who want to partner with the company.